PENGEMBANGAN WEBSITE MANAJEMEN TUGAS BERBASIS WEB UNTUK PENGUKURAN KINERJA SUMBER DAYA MANUSIA - Budi Pratomo, Arief (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2023)
This study aims to develop a web-based task management website to measure human resource performance. The website is designed to enhance the efficiency and effectiveness of task assignment and monitoring processes within an organization. It provides managers or administrators with the capability to assign tasks to staff members quickly and efficiently. Staff members, on the other hand, can access a comprehensive list of assigned tasks, track their progress, and record the time required for task completion. Additional features such as automated notifications, task prioritization, and task reassignment are also included. The development of the website follows the software development life cycle approach, which consists of analysis, design, implementation, and evaluation phases. Data for the research were collected through participatory observation, interviews with staff and managers, and performance data analysis before and after the website's implementation. Descriptive statistical methods were employed to analyze the collected data and measure the effectiveness of the website in improving human resource performance. The findings of this study will provide valuable insights into the impact of a web-based task management system on human resource performance. It is expected that the website will enhance task assignment efficiency, improve communication and coordination between managers and staff, and ultimately contribute to overall organizational productivity. The research serves as a valuable resource for organizations seeking to optimize their human resource management processes through web-based solutions.